(untitled) (Journal of Engineering, 2013)
The present study deals with the optimum design of self supporting steel communication towers. A special technique is used to represent the tower as an equivalent hollow tapered beam with variable cross section. Then this method is employed to find the best layout of the tower among prespecified configurations. The formulation of the problem is applied to four types of tower layout with K and X brace, with equal and unequal panels. The objective function is the total weight of the tower. The variables are the base and the top dimensions, the number of panels for the tower and member’s cross section areas. The formulations of design constraints are based on the requirements of EIA and ANSI codes for allowable stresses in the members and the allowable displacement at antenna position. The Sequential Unconstrained Minimization Technique (SUMT) is used to perform the process. Direct stiffness method is used for the analysis of the structure, with beam elements. The strain energy is used to derive the stiffness matrix for members of unsymmetrical cross section. A computer program in FORTRAN is developed to represent the tower as an equivalent beam, and generate the tower nodes and members, analysis, design and to find the optimum design. Four types of tower are studied with different load cases. The effects of earthquake and wind loadings are taken in two directions and two positions of antenna are considered in the process to seek the optimum design. The tower type of X-brace with unequal panels has the minimum weight compared with other types of tower and the optimum design is satisfied when the angle of main leg is equal to (87O).